Income Ratio of Lokan Search Fishermen (Geloina erosa) Families in the Village of Suka Maju, Air Periukan District, Seluma District - Suparyanto Widodo; Rika Dwi Yulihartika; Evi Andriani (UNIVED Press, Dehasen University Bengkulu, 2023)
The maritime and fisheries sector is one of the economic sectors that has a role in national economic development, especially in providing protein, earning foreign exchange and providing employment opportunities. The aim of this research is to determine the contribution to household income and to determine the contribution of local people to household income in Suka Maju Village, Air Periukan District, Seluma Regency. The methods in this research include primary data and secondary data. The research results show that the income of local fishermen in the Air Priukan District is quite high. Income for each person varies according to the number of lokans sold and the selling price of lokans. Lokan fishermen are people who get lokan from the sea. Their income level is more focused on how much they sell and how many days they sell. To get lots of lokans, you only need the skills to dive, swim and have the strength to breathe for a long time, so that loch seekers can easily reach the ground mixed with rocks, so that the river shells hide behind rocks and sand mixed with clay. The household income of Lokan Fishermen in Sukamaju Village, Air Priukan District, Seluma Regency is IDR 2,222,920 per year, consisting of the income of Lokan Fishermen of IDR. 1,137,904.99, meanwhile the income contribution of Lokan Fishermen is 53.64% of household income.